Methodology of using Linda's indices to assess the concentration of commodity markets - Muradyan, Arman; Muradyan, Hrayr (Bulletin of Yerevan University G: Economics, 2021)
Empirical studies show that the Herfindahl-Hirschman index HHI and indicators -sum of market shares of the k largest firms, do not fully describe all aspects of market concentration. In this paper, having studied the advantages and disadvantages of these two indicators, it was concluded that the Linda indices should also be added to these two indicators, the use of which can contribute to the implementation of more effective antitrust policy.
Keywords: competition; concentration estimation; Linda indices; oligopolistic core